2015
DOI: 10.15376/biores.10.1.1424-1433
|View full text |Cite
|
Sign up to set email alerts
|

Production of Particleboards with Bamboo (Dendrocalamus giganteus) Reinforcement

Abstract: The focus of this research was to study the utilization of residues from bamboo (Dendrocalamus giganteus) lamination in the manufacturing of panels for structural purposes. Bamboo particleboards were produced under three conditions: pure boards, reinforced with bamboo laminas, and with treated particles. Castor oil-based polyurethane was the resin binder, in view of using lower toxicity materials. The mechanical tests were performed according to Brazilian Standard (NBR) 14810-3 (2006) and European Standard (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 8 publications
(9 reference statements)
1
19
0
8
Order By: Relevance
“…This material is an important source of raw material for construction and furniture (Janssen 2000;Pereira and Beraldo 2007;Zaia et al 2015;De Almeida et al 2017). Bamboo acts as an option for laminate production, due to low cost, high efficiency, and environmental advantages, presenting a wide market potential to substitute other current raw materials (Huang et al 2015), such as steel, lumber, concrete, etc.…”
Section: Bioresourcescommentioning
confidence: 99%
See 1 more Smart Citation
“…This material is an important source of raw material for construction and furniture (Janssen 2000;Pereira and Beraldo 2007;Zaia et al 2015;De Almeida et al 2017). Bamboo acts as an option for laminate production, due to low cost, high efficiency, and environmental advantages, presenting a wide market potential to substitute other current raw materials (Huang et al 2015), such as steel, lumber, concrete, etc.…”
Section: Bioresourcescommentioning
confidence: 99%
“…Bamboo acts as an option for laminate production, due to low cost, high efficiency, and environmental advantages, presenting a wide market potential to substitute other current raw materials (Huang et al 2015), such as steel, lumber, concrete, etc. The utilization of bamboo laminae as reinforcement improved the panel performance (Zaia et al 2015), Cross-laminated timber (CLT) is a structural panel produced with 90° overlapping wooden layers that can contain 3 to 7 layers of wood (or more, increasing the panel density and cost), always in odd numbers, providing the dimensional stability and allowing the prefabrication of slab and wall panels. This composition offers high stiffness and strength in all directions.…”
Section: Bioresourcescommentioning
confidence: 99%
“…This adhesive has been used in Brazilian studies and has shown promising results, because it is more ecologically friendly than purely chemical-based adhesives such as ureaformaldehyde, whereas it uses castor beans, a natural material (Zaia et al 2015). Lastly, Dias (2008) emphasizes that the curing of this resin occurs at room temperature, but it could be accelerated with a temperature ranging from 60 to 90 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the investigated bamboo particleboards meet the normative requirements for medium density solutions and, in some cases, exceed the requirements, especially in Zaia et al (2015), where a MOR of 38.0 MPa and MOE of 5.9 GPa were found. These results are related to the higher density SR: synthetic resin; PF: phenol formaldehyde; UF: urea formaldehyde.…”
Section: Mechanical and Physical Propertiesmentioning
confidence: 89%
“…Although there are no competitive engineered bamboo industries in Brazil, a high local potential, regarding the bamboo plantation and commercialization, makes reasonable to perform scientific research related to the development of high value-added products using bamboo. In fact, several studies have been made in Brazil using agricultural waste for the particleboard production (Calegari et al 2007, Fiorelli et al 2012a, Fiorelli et al 2012b, Fiorelli et al 2014, Belini et al 2014, Valarelli et al 2014, Zaia et al 2015. Qisheng et al (2001) classified bamboo panels according to their material composition and product structure: bamboo-plywood products, laminated products (laminated bamboo from strips), chipboard products (bamboo chip/particleboard) and composite board products.…”
Section: Bamboo Particleboardsmentioning
confidence: 99%